2014
DOI: 10.1002/ece3.1167
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality determines interspecific parasite interactions in host populations

Abstract: The widespread occurrence of multiple infections and the often vast range of nutritional resources for their hosts allow that interspecific parasite interactions in natural host populations might be determined by host diet quality. Nevertheless, the role of diet quality with respect to multispecies parasite interactions on host population level is not clear. We here tested the effect of host population diet quality on the parasite community in an experimental study using Daphnia populations. We studied the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 99 publications
(202 reference statements)
2
49
0
1
Order By: Relevance
“…A further investigation showed that parasite fitness can be determined by diet‐quality‐dependent interspecific parasite interactions, when host population‐level effects are taken into account (Lange et al . ). This suggests that experimental host range studies should include the parasite's entire transmission cycle to better assess its ability for long‐term persistence in a host population.…”
Section: Introductionmentioning
confidence: 97%
“…A further investigation showed that parasite fitness can be determined by diet‐quality‐dependent interspecific parasite interactions, when host population‐level effects are taken into account (Lange et al . ). This suggests that experimental host range studies should include the parasite's entire transmission cycle to better assess its ability for long‐term persistence in a host population.…”
Section: Introductionmentioning
confidence: 97%
“…However, because the intensity of symptoms and level of virulence experienced by hosts is, in large part, context dependent (Scholthof 2007), it may be useful to consider these symptoms across environmental gradients that are relevant to nutrient recycling. Host nutrient supply could also directly affect parasite-host interactions with though its effects on parasite virulence (Vale et al 2011, Abu Kwaik andBumann 2013), parasite load (Bruno et al 2003, Frost et al 2008a, and interspecific parasite interactions (Lange et al 2014). Host nutrient supply could also directly affect parasite-host interactions with though its effects on parasite virulence (Vale et al 2011, Abu Kwaik andBumann 2013), parasite load (Bruno et al 2003, Frost et al 2008a, and interspecific parasite interactions (Lange et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…under stressful conditions, e.g., predation (stiBor 1992), temperature increase (geerts et al 2014), metal contamination (LoPes et al 2004). This "fecundity compensation" has also been identified for Daphnia sp.-parasite interactions (chaDwicK & LittLe 2005;cooPman et al 2014;Lange et al 2014). This can again be linked to an energy allocation perspective.…”
Section: Discussionmentioning
confidence: 85%
“…WFCD is a small coccoid parasite that infects the adipose tissue of Daphnia species (eBert 2005). The infection is transmitted horizontally, and severely impacts survival in Daphnia species (cooPman et al 2014;Lange et al 2014) and to a lesser extent fecundity upon disease progression. P. ramosa strains were isolated from the same pond as were the Daphnia clones, but from a later time (2012) than the clones were isolated (most recent clone isolates 2002).…”
Section: Daphnia Genotypes and Parasitesmentioning
confidence: 99%
See 1 more Smart Citation